2014
DOI: 10.7763/ijcce.2014.v3.304
|View full text |Cite
|
Sign up to set email alerts
|

Child and Adult Classification Using Ratio of Head and Body Heights in Images

Abstract: Pedestrian detection is a challenging problem. There are various researches to detect people in digital images. Besides, to recognize children from adults in digital platforms is helpful for applications which are created to people's good account. For instance, if Closed Circuit Television (CCTV) which is located on traffic lamb detects child who is walking through pedestrian way, system could make some adjustment in a good way. Aim of this article is to detect children and adults separately in digital images.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Age prediction from human body images was presented in [5] where authors used their training dataset which contained just 1500 elements. In the context of child detection, the method based on the ratio between head and body heights was also proposed in [6]. The greatest number of researches touched an area of gait-based human age classification ( [7], [8], [9]) but to our newest knowledge, there is any application for a single image age classification based on still body images.…”
Section: A Related Workmentioning
confidence: 99%
“…Age prediction from human body images was presented in [5] where authors used their training dataset which contained just 1500 elements. In the context of child detection, the method based on the ratio between head and body heights was also proposed in [6]. The greatest number of researches touched an area of gait-based human age classification ( [7], [8], [9]) but to our newest knowledge, there is any application for a single image age classification based on still body images.…”
Section: A Related Workmentioning
confidence: 99%
“…One of these is the head-to-body ratio, which is larger in children. Using the head-to-body ratio as a feature, Ince et al [17] performed age classification of pedestrians as child or adult. Additionally, children have shorter limbs, and their upper limbs appear closer to the ground.…”
Section: Biological Featuresmentioning
confidence: 99%
“…In 2001, Davis [14] classified pedestrians as adults or children based on their walking styles. Other early attempts on age estimation using vision-based gait include the works of [15], [16], [17], and [18] in 2005, 2010, 2014, and 2015 respectively. The first attempt on age estimation using sensor-based gait was made by Riaz et al [19] in 2015.…”
Section: Introductionmentioning
confidence: 99%
“…where kernel scale σ is a constant to adjust the width of the Gaussian function. Replacing y k SV(i) , y k with the kernel function, the solution in (14) becomes…”
Section: Svrmentioning
confidence: 99%
“…For example, Davis [7] showed the gait difference between an adult and a child in terms of leg length, stride width, and stride frequencies. Ince et al [14] showed that the head-to-body ratio of a child is different from an adult. Similar findings were also reported in [25] by analyzing the most widely used appearance-based gait representation (known as gait energy images (GEIs) [13] or averaged silhouettes [18]), which contains both gait and shape information.…”
Section: Introductionmentioning
confidence: 99%